دراسة تحرر الأورثوفوسفات وعلاقته بعاملي الزمن والأكسجين المنحل في أحواض ترسيب وتكثيف الحمأة - جناد, هيثم; منصور, باسم (Latakia University Journal -Engineering Sciences Series, 2018)
يعد هذا العمل دراسة حقلية ومخبرية لتأثير عاملي الزمن وتركيز الأكسجين المنحل على تحرر الأورثوفوسفات في المياه المعالجة الناتجة عن ترسيب وتكثيف الحمأة في محطة معالجة مياه الصرف الصحي في منطقة الرويمية في ريف اللاذقية. تم تقييم كفاءة المحطة في إزالة الفوسفور من المياه المعالجة، ودراسة تحرر الأورثوفوسفات وعلاقته بعاملي الزمن والأكسجين المنحل في حوضي الترسيب والتكثيف وفق ظروف المحطة. أجريت كذلك دراسة مخبرية لتحرر الأورثوفوسفات وعلاقته بزمن المكوث وتركيز الأكسجين المنحل، لعينات تحمل تراكيز أوليّة مختلفة للأورثوفوسفات هي: (20, 40, 60, 80) ملغ/ل.أظهرت النتائج انخفاض كفاءة إزالة الأورثوفوسفات في المحطة حيث بلغت33.3 % في شهر أيلول وَ 41.6 % خلال شهر تشرين الأول. كما أظهرت النتائج تحرر الأورثوفوسفات في أحواض الترسيب والتكثيف بازدياد زمن المكوث وبالتزامن مع انخفاض تركيز الأكسجين المنحل في كل منها. بالنسبة للعينات الخاضعة للمعالجة وفق شروط تجريبية والتي تحمل تراكيز أوليّة مختلفة للأورثوفوسفات 20، 40، 60، 80 ملغ/ل، بدأ تحرر الأورثوفوسفات بعد مرور 4 ساعات من بدء عملية الترسيب وبقيت تراكيز الأورثوفوسفات ضمن الحدود المسموح بها للمحطة حتى زمن 10 ساعات.لوحظ عند استخدام الترسيب الكيميائي للأورثوفوسفات بإضافة كلوريد الحديد تأخر في تحرر الأورثوفوسفات وتحرر جزئي فقط مرتبط بجرعة كلوريد الحديد المضافة. This work is a field and experimental study of effects of time and dissolved oxygen concentration factors on ortho-phosphate releasing in treated water resulting from sludge precipitation and thickening basins in Alruyemih wastewater treatment plant in the countryside of Latakia. Phosphorus removal efficiency from treated water in the plant has been evaluated and ortho-phosphate release and its relation to the time and dissolved oxygen factors in sludge precipitation and thickening basins have been studied according to plant conditions. An experimental studying of ortho-phosphate release and its relation to time and the dissolved oxygen factors for samples with different initial concentration of ortho-phosphate, which were 20, 40, 60, and 80 mg/l.Results have shown a decrease of ortho-phosphate removal efficiency in the plant, which were 33.3 % in September and 41.6 % in October. Results have also shown ortho-phosphate release in sludge precipitation and thickening basins with increasing of retention time and decreasing of dissolved oxygen concentration in these basins.For samples treated with experimental conditions of different initial concentrations of ortho-phosphate (20, 40, 60, and 80 mg/l), ortho-phosphate release has started after 4 hours of precipitation process beginning, and its concentrations have remained under allowed limits of the plant for 10 hours.A time delay of ortho-phosphate release beginning has noticed when the chemical precipitation of ortho-phosphate has used. An ortho-phosphate partial release has also noticed, which is related to ferric chloride dose added.